Immunostimulant Activities of Dioscorea esculenta L. Tubers Based on Phagocytic Activity and Lymphocyte Proliferation In Vitro - Ika Puspitaningrum; Muthi' Ikawati; Nanang Fakhrudin; Arief Nurrochmad (Majalah Obat Tradisional, 2025)
The immune system plays an important role for the body, especially in protecting it from exposure to bacteria, viruses, and other foreign bodies. Improving the immune system can be done by daily consumption of certain foods. Foods that can be developed into an immunostimulant are tubers, one of which comes from the genus Dioscorea. Dioscorea esculenta L., known as gembili tuber, is widely found in Indonesia, but has not been widely tested for its activity as an immunostimulant both against the innate and adaptive immune systems. This study aims to determine the immunostimulant activity of aqueous extract (AE), polysaccharide fraction (PF), and non-polysaccharide fraction (NPF) of gembili tubers against macrophage phagocytosis activity and lymphocyte proliferation. Test of phagocytosis activity and lymphocyte proliferation was performed in vitro by adding AE, PF, NPF gembili tubers 12.5, 50, and 100 mg/mL, inulin 100 µg/mL, and positive control 10 mg/mL as a comparison in macrophage cells and mouse lymphocyte cells. Phagocytosis activity was expressed in phagocytosis capacity and phagocytosis index, while lymphocyte proliferative activity was expressed in proliferative stimulating index. The results showed that AE, PF, and NPF could increase macrophage phagocytosis activity, with the highest activity observed at AE 100 μg/ml, PF 100 μg/ml, and NPF 12.5 μg/ml. AE, PF, and NPF were also shown to increase lymphocyte proliferation activity, with the most significant enhancement observed at AE 12.5 μg/mL, PF 12.5, and NPF 50 μg/mL.